If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 4x + -8 = 48 Reorder the terms: 12 + -8 + 4x = 48 Combine like terms: 12 + -8 = 4 4 + 4x = 48 Solving 4 + 4x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4x = 48 + -4 Combine like terms: 4 + -4 = 0 0 + 4x = 48 + -4 4x = 48 + -4 Combine like terms: 48 + -4 = 44 4x = 44 Divide each side by '4'. x = 11 Simplifying x = 11
| ad= | | y=x^3-27x+4 | | 6(4-8a)+7=-17 | | -3x^2+8x-2=0 | | (7)(4+2x)=56 | | 64m^8-49n^6=0 | | -(9x-8)= | | -6x-5x=-11 | | -8=3x+4 | | 12x+6y=60 | | -15x^3+40x^2+35x=0 | | -35=n-17 | | -6=3(3+k) | | 6-(-10)= | | 5-4x-5=-8 | | -77=8x+3 | | -126=-18r | | -11=x-6 | | w^2-6w-8=0 | | 7a+8=57 | | 4(3-x)-8=5-(3x-2) | | 4u^2-25u+25=0 | | 53+(-18)= | | 52+-50= | | 5.4c+6=0.6(9c+10) | | 3t+7=13 | | 5x-6x-5=72 | | -3+14= | | 4d-6=2(3d-4) | | x^2-14x+196=0 | | -25+25= | | 78=-5x+19 |